2005
DOI: 10.1128/iai.73.9.5402-5409.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Cloning, Expression, and Characterization of the Gene for Plasmodium knowlesi Surface Protein Containing an Altered Thrombospondin Repeat Domain

Abstract: Proteins present on the surface of malaria parasites that participate in the process of invasion and adhesion to host cells are considered attractive vaccine targets. Aided by the availability of the partially completed genome sequence of the simian malaria parasite Plasmodium knowlesi, we have identified a 786-bp DNA sequence that encodes a 262-amino-acid-long protein, containing an altered version of the thrombospondin type I repeat domain (SPATR). Thrombospondin type 1 repeat domains participate in biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 37 publications
5
25
0
Order By: Relevance
“…In P. falciparum, PfSPATR is expressed at several stages of the parasite life cycle, an important consideration for vaccine development (18). Furthering its vaccine potential, Plasmodium SPATR is immunogenic in naturally infected and immunized volunteers, and antibodies to recombinant SPATR block sporozoite invasion (18,21). These findings suggest a role in invasion, which is consistent with the ability of Plasmodium SPATR to bind HepG2 hepatoma cells (18,21).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…In P. falciparum, PfSPATR is expressed at several stages of the parasite life cycle, an important consideration for vaccine development (18). Furthering its vaccine potential, Plasmodium SPATR is immunogenic in naturally infected and immunized volunteers, and antibodies to recombinant SPATR block sporozoite invasion (18,21). These findings suggest a role in invasion, which is consistent with the ability of Plasmodium SPATR to bind HepG2 hepatoma cells (18,21).…”
supporting
confidence: 68%
“…Furthering its vaccine potential, Plasmodium SPATR is immunogenic in naturally infected and immunized volunteers, and antibodies to recombinant SPATR block sporozoite invasion (18,21). These findings suggest a role in invasion, which is consistent with the ability of Plasmodium SPATR to bind HepG2 hepatoma cells (18,21). Herein, we further dissect the significance of TgSPATR in infection by genetically ablating it in T. gondii.…”
supporting
confidence: 62%
“…This protein binds to hepatoma cells such as HepG2; antibodies directed against it have been able to inhibit P. falciparum sporozoite invasion of liver cells [48,150]. It has been reported that PfSPATR has also bound to human RBCs and to an anopheline mosquito larvae pluripotent cell line [150], thereby highlighting its importance as ligand during host-cell recognition and invasion.…”
Section: Secreted Protein With An Altered Thrombospondin Repeat (Spatmentioning
confidence: 97%
“…Many invasive stages of Plasmodium have been found to contain one or more thrombospondin type-1 repeat (TSR) domain [5], suggesting the possible role of this domain in sporozoite motility and hepatocyte invasion. An altered version of the thrombospondin repeat domain was first found in Plasmodium yoelii [6,7] and named the surface protein of altered thrombospondin repeat (SPATR). Orthologue of this protein has also been identified in P. knowlesi and named the pk SPATR.…”
Section: Introductionmentioning
confidence: 99%
“…SPATR protein is expressed during many stages of the P. knowlesi life cycle, including the sporozoite, merozoite and gametocyte stages [6]. Importantly, it is expressed on the cell surface during the sporozoite stage, where it is involved in liver cell invasion.…”
Section: Introductionmentioning
confidence: 99%